SIMULASI NUMERIK DAN EKSPERIMEN PERAMBATAN RETAK MELINTANG PADA STRUKTUR KOMPOSIT BAMBU DENGAN MENGGUNAKAN ELEMEN KOHESIF - Nishfu Arobi, Ilham
applications to produce lightweight structures, its more environmentally friendly characteristic is the main basis for the development of natural fiber composites from various materials including bamboo that is widely available in Indonesia. In order to adjust to its potential application, it is necessary to understand the characteristics of bamboo composites including in this case the mechanism of damage that can occur. As a composite material, one mode of damage that needs to be understood in bamboo is the occurrence of transverse cracks, namely the mode of crack damage that appears and propagates in the matrix. In this study, an analysis was conducted to find out the phenomenon of initiation and propagation of transverse cracks that occur in bamboo composite structures. The study was conducted on a semi-circular arc bend (SCAB) specimen and subjected to three-point bending. To find out the effect of the initial crack, a specimen is used that is given an initial crack of 2 mm. Numerical studies are conducted to study the use of cohesive elements in modeling cracks. Experimental studies were also conducted for validation of numerical modeling. Numerical simulation results show the likeness of experiments on the phenomenon of initiation and propagation of transverse cracks in the middle of the first appeared. While related to the phenomenon of the next crack on the side shown in experimental results, it cannot be modeled on numerical simulations in this study. The load-displacement graph from simulation does not show a clear load drop when the crack is first initiated. While in the experiment occurred several times load drop due to initiation of cracks in the middle and side of the bamboo. These results suggest more experimental studies are needed to produce characteristics of bamboo materials that can be used for better cohesive element modeling.